Short-Term Treatment of Metformin and Glipizide on Oxidative Stress, Lipid Profile and Renal Function in a Rat Model with Diabetes Mellitus - Abdel-Moneim Hafez Abdel-Moneim; Mohamed Faisal Lutfi; Ashwag Saleh Alsharidah; Gehan Shaker; Waleed Faisal; Ahmed A. H. Abdellatif; Osamah Al Rugaie; Khalid M. Mohany; Safaa Yehia Eid; Mahmoud Zaki El-Readi; Mansour Alsharidah (Applied Sciences, 2022)
Background: Oxidative stress, lipid profile and renal functions are well-known conventional risk factors for diabetes mellitus (DM). Metformin and gliclazide are popularly used monotherapy drugs for the treatment of DM. Aims: This study aims to assess the short-term treatment of single and dual therapy of glipizide/metformin on oxidative stress, glycemic control, serum lipid profiles and renal function in diabetic rats. Methods: DM was induced in rats with streptozotocin (STZ), then five different treatments were applied, including group I (untreated healthy control), group II (diabetic and untreated), group III (diabetic and treated with metformin), group IVI (diabetic and treated with glipizide) and group V (diabetic and treated with a combination of metformin and glipizide. Lipid peroxidation (LPO), nitric oxide (NO), total antioxidant capacity (TAC), fasting blood glucose (FBG), glycated hemoglobin (HbA1c), total cholesterol, triglycerides, high-density lipoprotein (HDL), low-density lipoprotein (LDL), creatinine and urea were measured. Results: Compared to the untreated DM group, FBG and HbA1c were significantly reduced in the DM groups (p < 0.01) treated with metformin (159.7 mg/dL & 6.7%), glipizide (184.3 mg/dL & 7.3%) and dual therapy (118 mg/dL & 5.2%), respectively. Treatment with dual therapy and metformin significantly decreased LPO and NO levels but increased TAC in diabetic rats more than glipizide compared to untreated diabetic rats. Furthermore, metformin (19.8 mg/dL, p < 0.001), glipizide (22.7 mg/dL, p < 0.001), and dual therapy (25.7 mg/dL, p < 0.001) significantly decreased urea levels in the treated rats compared to untreated DM rats (32.2 mg/dL). Both drugs and their combination exhibited a substantial effect on total cholesterol, HDL, LDL and atherogenic index. Conclusions: These results suggest that the therapeutic benefits of metformin and glipizide are complementary. Metformin exhibited superior performance in improving glycemic control and decreasing oxidative stress, while glipizide was more effective against dyslipidemia. These findings could be helpful for the treatment of future vascular patients, antilipidemic medicines and antioxidant therapy to improve the quality of life.